Critical Approaches to Postcolonialism - Dhobi, Saleem (Patan Pragya, 2024)
This paper examines distinctive measurements of post colonialism and analyzes the point of view of postcolonial scholars in a way that the concepts on post colonialism and colonialism within the modern scholarly dialog can be comprehended. The speculations and approaches to scholarly examination have made the discourse on post colonialism hot and far from being obviously true as the nations and journalists of the colonized countries have entered into a preface that's expected to be free for basic and imaginative dialogs. The perspective the paper has attempted is exploratory because it includes the basic viewpoints of the researchers such as Che Guevara, Rumina Sethi, Robert Youthful, Arif Dirlik, Amar Acheraiou, Aijaz Ahmad, and Homi Bhabha extending from Europe to Asia. Postcolonial scholars look for the reasons of what happens when two societies collide with each other. Their concern is repercussions of social struggle. Decolonization may be a preparation of vanishing colonizers from the lands they had colonized at a time and ruled on the local individuals. In spite of the fact that decolonization has wrapped up its course, the scholars lock in the perusers within the clash of civilization as experienced by the colonized and caused by the colonizers within the colonized countries within the post-colonial period. The article lays the streams on the issue i.e. post colonialism and its unmistakable flow as seen and conceived by the postcolonial scholars. The paper has utilized a topical approach to discuss post colonialism.